The Qur'an in The Javanese Tomb Inscription: Historical, Cultural and Meaning Studies - Samsul Ariyadi (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study examines the existence and variations of Qur'anic verses inscribed on tombs in the Java region. With a rich historical background, the area is a silent witness to the process of acculturation that results in a unique cultural identity, where Islam interacts with local traditions. Historical and cultural studies were carried out using textual analysis methods and epigraphic field documentation, which allowed researchers to collect data from various burial sites as well as document this phenomenon in more depth. The research aims to uncover the historical background, context of the spread of Islam, and the dynamics of Javanese culture which is reflected through the variations of Qur'anic verses on tomb inscriptions. By examining these variations, we can see how the Javanese people interpret Islamic teachings in the context of their local beliefs and practices. The findings of this study show that there is an interaction between Islamic traditions and local culture, where religious values are combined with symbols of beliefs and social structures of Javanese society. The results of the epigraphic analysis reveal the existence of variations in the writing and interpretation of verses that have important implications for the study of cultural history and the spread of Islam in Indonesia. In addition, this study also provides insight into the shift in social values that occur in the transmission of Islamic teachings to Javanese society. This process involves not only the spiritual aspect, but also the much broader social and cultural effects, which have shaped the way of life of people throughout the ages. By delving deeper into the variations of Qur'anic verses on the inscriptions, we can understand how the community adapted and embraced the teachings of this new religion, creating a synthesis between local faith and tradition that continues to this day.